Analysis of Losses Due to Load Unbalance in a 2000 kVA Transformer at Supermall Mansion 2 Tower Tanglin Surabaya - Reza Sarwo Widagdo; Aris Heri Andriawan (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2023)
The load unbalance causes a neutral current, the current flowing in the neutral conductor will cause an increase in losses in the transformer. The greater the losses incurred, the efficiency and reliability of the transformer will decrease. Based on this, a study was conducted on analyzing the losses on distribution transformers at Supermall Mansion 2 Tower Tanglin which aims to determine the percentage value of transformer loading, the value of transformer imbalance, the value of transformer losses, and the value of transformer efficiency. This is done so that the value of the installed transformer does not exceed the applicable SPLN value. During the measurement, it was found that the percentage value of the transformer loading was 38.88% during the daytime and 48.89% at night (maximum SPLN 80%, minimum 40%). The load unbalance value is 11.66% during the daytime and 10.33% at night (SPLN is categorized as good if < 10%). Copper losses (Pcu) are 91.3 kW during the daytime and 94.2 kW at night. The value of losses due to neutral currents is 0.134 kW with a percentage of 0.0071% during the daytime and 0.173 kW with a percentage of 0.0090% at night. The percentage of the current value in the neutral conductor is 26.36% during the day and 24.04% at night (SPLN is categorized as good if < 20%).